Simultaneous Detection of Ammonium and Nitrate in Environmental Samples Using on Ion-Selective Electrode and Comparison with Portable Colorimetric Assays - Jittima Choosang; Apon Numnuam; Panote Thavarungkul; Proespichaya Kanatharana; Tanja Radu; Sami Ullah; Aleksandar Radu (Sensors, 2018)
Simple, robust, and low-cost nitrate- and ammonium-selective electrodes were made using substrate prepared from household materials. We explored phosphonium-based ILs and poly (methyl methacrylate)/poly(decyl methacrylate)(MMA-DMA) copolymer as matrix materials alternative to classical PVC-based membranes. IL-based membranes showed suitability only for nitrate-selective electrode exhibiting linear concentration range between 5.0 × 10−6 and 2.5 × 10−3 M with a detection limit of 5.5 × 10−7 M. On the other hand, MMA-DMA—based membranes showed suitability for both ammonium- and nitrate-selective electrodes, and were successfully applied to detect NO3− and NH4+ in water and soil samples. The proposed ISEs exhibited near-Nernstian potentiometric responses to NO3− and NH4+ with the linear range concentration between 5.0 × 10−5 and 5.0 × 10−2 M (LOD = 11.3 µM) and 5.0 × 10−6 and 1.0 × 10−3 M (LOD = 1.2 µM), respectively. The power of ISEs to detect NO3− and NH4+ in water and soils was tested by comparison with traditional, portable colorimetric techniques. Procedures required for analysis by each technique from the perspective of a non-trained person (e.g., farmer) and the convenience of the use on the field are compared and contrasted.